Comparative emission study by real-time congestion monitoring for stable pollution policy on temporal and meso-spatial regions in Delhi. (1st July 2019) - Mishra, Sumit; Kushwaha, Ashutosh; Aggrawal, Devesh; Gupta, Ankit
Abstract: Rapid industrialization, urbanization, and motorization lead to hiking of air pollution in various mega cities including Delhi, India. Studies done to analyze pollution suggests that vehicle exhaust emissions are major contributor to the urban air quality along with many other comparable sources. Hence to check instantaneous pollution increment, government aims to reduce vehicle emission. Traditional policies are working at times for holding sudden increase but long-term effects are not seen which need meso-spatial and small temporal policy. For optimizing meso-spatial policies implementation, many intricacies related to moving and stationary sources in near real-time have to be monitored including vehicular emission, itself. Analyzing these moving source emissions on the meso-spatial level is challenging. Therefore, the present study is an attempt to first understand the need of meso-spatial and near real-time checking policy and then leveraging the usage of previous region specific pollutant survey reports to map real-time pollution monitoring parameters. For that, a real-time vehicle monitoring strategy is proposed to map city-wide traffic congestion and emission using crowd-source data of Google Maps. For comparative study of different meso-spatial regions real-time moving source pollutant parameter 'μ' is calculated using a factor 'F'. Also, the different effects of congestion on vehicular emission in two different meso-spatial areas of Delhi is presented using comparative case study. Analysis of case study revealed that Anand Vihar area is more prone to vehicle emission variability in case of congestion fluctuation. Further the discussion of short temporal and spatial emission calculation, for weekly pollution evaluation is presented in the paper. This will be helpful to the authorities in formulating technological, institutional and traffic management policies. Highlights: Traditional pollution checking policy and different emission models are discussed for Delhi region. A methodology to map real-time congestion for city-wide area on small tempo-spatial basis is provided. A factor 'F' is introduced for relating congestion to vehicular and dust emission. Vehicle proportionate area specific moving source emission 'μ' is calculated and analyzed by comparative emission study. Suggestions on checking policy and the methodology to judge their effectiveness for immediate action is provided.